A new kind of relativity: Compensated delays as phenomenal blind spots. Issue 3 (December 2015) - Vrobel, Susie
Abstract: The French phenomenologist Merleau-Ponty identified the human body as the blind spot of perception and cognition. Being situated in its environment both spatially and temporally, the body forms a primordial field of presence, which is transparent from the obserpant's 1 perspective and therefore creates a sytemic blindness. This paper is primarily concerned with what Merleau-Ponty calls the pulse of the duration of the body, which, in his view, "impregnates" our perception. This notion of duration will be described in terms of the temporal extensions of an embodied obserpant. For biological systems, these extensions may be measured in the obserpant's temporal endo-sphere, a time cone, which extends in two dimensions: succession and simultaneity (Δtlength and Δtdepth, respectively). Obserpants are described not as having, but being a model of the world (including themselves). The perception of Δtlength and Δtdepth results in a fractal temporal structure, which correlates with successive and instantaneous perception. This temporal structure becomes important during temporal recalibration, i.e. delay compensation. During such processes, the distribution of the temporal dimensions succession and simultaneity may vary from one obserpant's Now to another's. Furthermore, recalibration provides a window in which the obserpant's Now may be tipped towards either temporal dimension. We can measure the difference between obserpant A's temporal extension and that of obserpant B in Δtlength and Δtdepth . The complexity of an obserpant's temporal perspective – his temporal interface – can thus be compared and quantified by the size of his time cone. The units of this measurement are the number of compensated and uncompensated delays. During temporal recalibration, an obserpant can turn succession into simultaneity and vice-versa. Moreover, what is successive in obserpant A's Now may be simultaneous for obserpant B and vice-versa. This discrepancy can be modelled as time cones which display a new kind of (Δtlength –Δtdepth –) relativity. This new kind of relativity arises from the oberpants' inability to spot the systemic blindness that manifests itself in anticipated, i.e. compensated, delays.